Regularities of plaque stabilization in various scenarios of neointimal calcification and vascularization - N. Yu. Osyaev; L. A. Bogdanov; R. A. Mukhamadiyarov; A. R. Shabaev; D. K. Shishkova; V. E. Markova; O. V. Gruzdeva; A. G. Kutikhin (Российский кардиологический журнал)
Aim. To study the relationships between phenotypes of extracranial arteries' plaques (stable/unstable), their calcification and its causes, in particular, vascularization.Material and methods. The study included 88 patients: patients (n=44) with ischemic stroke and those (n=44) with chronic brain ischemia. In all subjects, the parameters of systemic mineral homeostasis were assessed (total and ionized calcium, phosphate, total protein, albumin, and calcification propensity). Atherosclerotic plaques have been obtained during carotid endarterectomy, fixed in formalin, postfixed in 1% osmium tetroxide, stained in 2% osmium tetroxide, dehydrated in ascending ethanol series and acetone, stained with 2% alcoholic uranyl acetate and embedded into epoxy resin with its further polymerization. Epoxy resin blocks were grinded, polished, counterstained with Reynolds' lead citrate and sputter coated with carbon. Sample visualization was performed employing backscattered scanning electron microscopy. Number and area of calcium deposits and neointimal vessels were quantified using ImageJ. Statistical analysis was carried out using Mann-Whitney U-test and Spearman's rank correlation coefficient.Results. It was found that area of neointimal calcification, but not number of calcium deposits, was associated with the stable plaque phenotype. The stabilizing effect of calcification was manifested in retarding stenosis associated with plaque rupture and stroke. Calcification extent directly correlated with total and local plaque vascularization, which have been associated with unstable and stable plaque phenotype, respectively. In addition, plaque calcification negatively correlated with total protein and albumin, thereby reflecting the impaired systemic mineral homeostasis.Conclusion. Atherosclerotic plaque calcification and active local vascularization reduce stenosis extent and stabilize plaque. In contrast, total plaque calcification contributes to the atherosclerosis progression and promotes major acute cardiovascular events.